ØªØ¯Ø±ÙŠØ³ ÙƒØªØ§Ø¨ "Ø§Ù„Ù…ØØ§Ø¯Ø«Ø© ÙˆØ§Ù„Ù…Ø·Ø§Ù„Ø¹Ø© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ø§Ù„Ø¬Ø²Ø¡ Ø§Ù„Ø£ÙˆÙ„" ÙÙŠ ØªÙ†Ù…ÙŠØ© Ù…Ù‡Ø§Ø±Ø© Ø§Ù„ÙƒÙ„Ø§Ù… Ù„Ù„Ù…Ø³ØªÙˆÙ‰ Ø¨Ù…Ø¹Ù‡Ø¯ Ø¯Ø§Ø± Ø§Ù„Ù„ØºØ© ÙˆØ§Ù„Ø¯Ø±Ø§Ø³Ø§Øª Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© Ø³Ù†ÙŠÙ†Ø§Ù† Ø¨Ø§Ù…ÙŠÙƒØ§Ø³Ù† - Moh. Hasyim Asy'ari (Tarling : Journal of Language Education, 2019)
The topic of this research is "Learning the Book of Al-Muhadasah Wa Muthala'ahAl-Arabiyah Juz Awwal for the Development of Maharah Kalam in the IslamicBoarding School Darul Lughah Waddirosatil Islamiyah, Seninan Akkor PelengaanPamekasan Madura, East Java". Every year there must be acceptance of newsantri in all of the rapidly developing huts in Indonesia, The new santri usuallyfind it difficult to speak Arabic because they don't know much about Arabicbefore entering pondok. This research aim to know the steps of learning and thepositive factors that influence the learning. This research use qualitative researchmethods. The results of this study are as follows: 1. Learning Steps to the Book"Al-Muhadasah Wa Muthala'ah Al-Arabiyah Juz Awwal" the teacher greets,remembering the students last lesson, giving new teaching material, the teacherreading the Muhadasah text and the students practiced the Muhadasah text thestudents were allowed to ask about the difficult mufrodat, the students translatedthe muhadasah text according to their abilities, then the teacher interpreted thewhole of the Muhadasah text. then the teacher gives training about sometimesthe teacher gives Arabic language games, the teacher tells students to memorize the muhadasah text and tells them to have two or two in front of the class, at the end of the lesson the teacher gives advice and motivation. 2. There are twopositive factors in the Learning of the Book "Al-Muhadasah Wa Muthala'ahAl-Arabiyah Juz Awwal" namely internal and external factors, internal factorsnamely: provisional teachers, the use of learning methodologies and appropriateteaching materials, students are eager to learn. External factors are: the scope ofthe Arabic language contained in the cottage.